МИРОВОЗЗРЕНЧЕСКИЕ ТРАНСФОРМАЦИИ В ЭПОХУ ПОСТИНДУСТРИАЛЬНОГО ОБЩЕСТВА - R. Y. Chyhur (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the research is to analyze concepts and essential characteristics of post-industrial society, which is generated by new anthropological measurements and ideological issues. Information society is proposed to consider as a stage of social development, which is characterized by comprehensive information of social structures and which is replacing the post-industrial. Number of signs on which postindustrial society is different from previous stages of social progress are identified. The fundamental changes in various social spheres are determined by the method of comparative analysis of known scientific theories. Conceptual exploration of leading scholars of post-industrial and information society stages development as D. Bell and M. Kastels are analyzed. The connection between economy and culture, economy and social transformation, which are represented in their works were solved. Availability of information, awareness of various social groups, media development, the existence of opportunities for rapid feedback – all these changes occur not only in the society, but also some of its scope and structure, including education, labour, intellectual abilities, values, family. The author emphasizes the fundamental transformation of ideological nature. They affect on the destruction of social structures and classical concepts. As a conclusion, it is argued the need to expand and to deep anthropological research, which is caused by the essence of the post-industrial stage of development.